Nghiên cứu ứng dụng phân hủy chất màu công nghiệp trong thực phẩm bằng vật liệu xúc tác quang hóa khả kiến Zn/ZnO/TiO2-Ag - Trường, Nguyễn Xuân; Minh Diệp, Nguyễn Thị; Quỳnh, Trần Thu; Chính, Huỳnh Đăng (Vietnam Journal of Chemistry, 2015)
Ag-doped TiO2 amorphous composite film coupled with metal oxide semiconductor ZnO on Zn-slide as a novel visible light photocatalyst is synthesized. The material is characterized using various analytical techniques such as X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDS) and Diffusive Reflectance Spectroscopy (DRS). It is indicated that the presence of the dopant, Ag, on Zn/ZnO/TiO2 film enhances its catalytic activity in VIS region. For environmental application, the photocatalytic activities of the material are evaluated by degradation of an artificial dye, tartazine, under sunlight. Furthermore, the effect of pH and H2O2 as an oxidizing agent on the degradation efficiency of the material is also investigated. The results show the optimal conditions for the photodegradation of the tartazine 0.5 mg sample are pH 5 and 3 ml H2O2 10 % in 6-hour irradiation.